Malaysian firm performance and shareholder wealth creation : comparative analysis of Economic Value Added and traditional performance measurement - Imani binti Mokhtar (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
This study empirically examined the claim of the superiority of value-based measure, Economic Value Added (EVA) against the traditional performance measures, Return on Equity (ROE) and Earnings per Share (EPS), in relation to the shareholder wealth creation (stock return) based on different industries in Malaysia. In addition, this study investigated the determinants of firm performance by employing both value-based and traditional performance measures across different industries. One of the pertinent investigations was on the influence of the potential expropriation by the majority shareholders towards minority shareholders, better known as the principal-principal conflict, which has become more prevalent in the emerging markets. The influence of the identity of majority shareholders on the firm performance was also explored. Furthermore, this study examined the impact of board governance mechanisms on the firm performance in a high ownership concentration structure. A sample of 492 Malaysian public listed firms, categorized according to their respective industries during the period of 2006 to 2015, was selected. Pooled ordinary least square (OLS), fixed effects, and random effects model were employed in identifying the best estimation model. The relative information content discovered that EVA outperformed the traditional performance measures in association with the stock return in most of the industries. The incremental information content revealed that one of the EVA components, namely capital charge, was the most significant component in relation to stock return in many industries. There was also significant evidence on the existence of incremental information content between paired EVA components in explaining the stock return. Additionally, this empirical study found inconsistent results pertaining to the determinants of firm performance across different industries. Among others, the principal-principal conflict was shown to have a significant negative impact on the firm performance only in one of the industries. Furthermore, the identity of the majority owners and board governance mechanisms were significant in relation to the firm performance of different industries. Most importantly, the results indicated that the traditional performance measures fit better than the value-based measure in assessing the determinants of firm performance across all industries. In terms of the managerial or practical implications, this study demonstrated the significance of EVA and its components in predicting the shareholder wealth creation. The important determinants of firm performance which the firm managers, policymakers, and regulators should focus on were also identified. In conclusion, corporate governance mechanisms relating to the ownership concentration and the identity of majority owners were imperative in the emerging economies, such as Malaysia.